Ferrokinetics in Patients with Rheumatoid Arthritis (Eurasian Medical Research Periodical, 2023)
Rheumatoid arthritis (RA) is an inflammatory disease of the joints, the main symptom of which is the development of symmetrical synovitis with a tendency to destructive changes in the joints, which affects an average of 1-2% of the world's population. The study included 134 patients, which were divided into two groups I (n=70) - RA patients without anemia and II (n=64) - RA patients with anemia. The values of hemoglobin level, total iron-binding capacity (TIBC) of blood, ferritin level, and values of soluble blood transferrin receptors were assessed. The presence of anemia in patients with RA is accompanied by noticeable changes in the exchange of iron in the blood. The most pronounced changes in peripheral blood parameters and iron metabolism parameters were observed in patients with the articular-visceral form